In Search of the Functions of the Legal System: Axiomatic and Methodological Stages - Mario Krešić (Acta Universitatis Carolinae. Iuridica)
The theory of artifacts can be understood as primarily focusing on function when counting something as an artifact. With that starting point, projects aimed at the identification of the function of law contribute to arguments about categorizing law as an artifact. The purpose of this study is to highlight the challenges of this endeavor. Before beginning with search for law-functions, questions about the postulates on the relations between an artifact, law, and function (axiomatic stage) have to be addressed and the proper methodological approach must be found which is capable of addressing the contingency problem (methodological stage).